Exploring Teacher Organizational Commitment for Promoting Sustainable Development in Higher Education: A Systematic Literature Review and Analysis of Theories and Methodologies in Chinese Studies - Yue, Liu; Alias, Bity Salwana; A. Hamid, Aida Hanim (Journal of Ecohumanism, 2025)
Teacher organisational commitment (TOC) is a key factor influencing teachers’ professional stability and teaching quality, and it is important for achieving sustainable development in higher education. However, systematic analyses in this area are insufficient. Therefore, this study adopted the PRISMA framework to conduct a systematic literature review, focusing on empirical studies on the COVID-19 pandemic and its post-epidemic period. Relevant literature was screened from Scopus, Web of Science, Wiley, and ScienceDirect, resulting in 11 peer-reviewed studies from the context of higher education in China, this study aims to explore the mainstream research theories and methodologies on TOC from a Chinese perspective and discuss the different roles TOC has played in various research. Exploring the current state in China, this study enhances the theoretical and practical understanding of TOC and delivers actionable insights for school administrations and policymakers to promote sustainable development in higher education. The study also offers recommendations for future research to investigate TOC in various cultural contexts further, thereby supporting international perspectives.